2011
DOI: 10.1093/jxb/err389
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of a wheat MYB transcription factor gene, TaMYB73, improves salinity stress tolerance in Arabidopsis thaliana

Abstract: MYB transcription factors (TFs) play pivotal roles in the abiotic stress response in plants, but their characteristics and functions in wheat (Triticum aestivum L.) have not been fully investigated. A novel wheat MYB TF gene, TaMYB73, is reported here based on the observation that its targeting probe showed the highest salinity-inducibility level among all probes annotated as MYB TFs in the cDNA microarray. TaMYB73 is a R2R3 type MYB protein with transactivation activity, and binds with types I, II, and IIG MY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
92
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(99 citation statements)
references
References 46 publications
3
92
0
Order By: Relevance
“…A yeast-one-hybrid assay was performed to study the transcriptional activation as described by He et al (2012). Full-length SbMYB15 cDNA was cloned in pGBKT7 followed by transformation in AH109 cells.…”
Section: Transactivation Assay Of Sbmyb15 In Yeast Cellsmentioning
confidence: 99%
“…A yeast-one-hybrid assay was performed to study the transcriptional activation as described by He et al (2012). Full-length SbMYB15 cDNA was cloned in pGBKT7 followed by transformation in AH109 cells.…”
Section: Transactivation Assay Of Sbmyb15 In Yeast Cellsmentioning
confidence: 99%
“…Plant stress tolerance is controlled by at least six signal transduction pathways (three ABA dependent and three ABA independent) in response to drought, high salinity and cold stress (Shinozaki and Yamaguchi-Shinozaki 2007). Both ABA-dependent and ABAindependent regulatory systems induce the expression of early response transcriptional activators, which then activate downstream stress tolerance genes (Zhu 2002, He et al 2012, Puranik et al 2012. Previous studies have characterized members of the APETELA2 (AP2), bZIP, NAC and MYB families of transcription factors in Arabidopsis and rice for their regulatory roles in response to abiotic stresses in plants (Abe et al 2003, Sakuma et al 2006, Hu et al 2008, Yang et al 2012, and additional studies demonstrated that transgenic plants that overexpress genes encoding transcription factors can greatly enhance the tolerance of plants to various abiotic stresses, such as salinity, cold and drought (Dubouzet et al 2003, Nakashima et al 2007, Xiang et al 2008, Hao et al 2011, He et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Both ABA-dependent and ABAindependent regulatory systems induce the expression of early response transcriptional activators, which then activate downstream stress tolerance genes (Zhu 2002, He et al 2012, Puranik et al 2012. Previous studies have characterized members of the APETELA2 (AP2), bZIP, NAC and MYB families of transcription factors in Arabidopsis and rice for their regulatory roles in response to abiotic stresses in plants (Abe et al 2003, Sakuma et al 2006, Hu et al 2008, Yang et al 2012, and additional studies demonstrated that transgenic plants that overexpress genes encoding transcription factors can greatly enhance the tolerance of plants to various abiotic stresses, such as salinity, cold and drought (Dubouzet et al 2003, Nakashima et al 2007, Xiang et al 2008, Hao et al 2011, He et al 2012). In addition, many genes are activated by transcription factors, such as late embryogenesis abundant (LEA) class genes (RD29B and RAB18) and proline biosynthetic genes (P5CS), and the activation of these genes can protect plants from oxidative damage due to osmotic stress, ionic toxicity and oxidative stress (Strizhov et al 1997, Bartels and Sunkar 2005, Szabados and Savouré 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, AtMYB15 was demonstrated to be associated with cold stress tolerance [18]. TaMYB33 and TaMYB73 from Triticum aestivum exhibited enhanced salinity tolerance [19,20]. AtMYB13, AtMYB15, AtMYB33, and AtMYB101 of Arabidopsis were implicated in phytohormone ABA-mediated responses to environmental signals [21].…”
Section: Introductionmentioning
confidence: 99%